Antibodies to yeast Sm motif 1 cross-react with human Sm core polypeptides - Bahia, D.; Font, J.; Khaouja, A.; Carreras, N.; Espuny, R.; Cicarelli, RMB; Ingelmo, M.; Bach-Elias, M. (Blackwell Science, 1999)
Two regions common to all UsnRNP core polypeptides have been described: Sm motif 1 and Sm motif 2. Rabbits were immunized with a 22 amino-acid peptide containing one segment of Sm motif 1 (YRGTLVSTDNYFNLQL-NEAEEF, corresponding to residues 11-32) from yeast F protein. After immunization, the rabbit sera contained antibodies that not only reacted specifically with the peptide from yeast F protein but also cross-reacted with Sm polypeptides from mammals; that is, with purified human U1snRNPs. The results suggest that the peptide used and human Sm polypeptides contain a common feature recognized by the polyclonal antibodies. A large collection of human systemic lupus erythematosus sera was assayed using the yeast peptide as an antigen source. Seventy per cent of systemic lupus erythematosus sera contain an antibody specificity that cross-reacts with the yeast peptide.
Keywords: autoimmunity; epitope mapping; peptide-ELISA; Sm motif 1; UsnRNPs